Soft vortex spinning fabric and spinning process
By using composite monomers in the vortex spinning fabric to form a graft copolymer and using silane-modified nanosilicon dioxide to form a reinforcement layer on the yarn, the problem of insufficient yarn flexibility and wear resistance in the traditional vortex spinning process is solved, and higher flexibility and wear resistance are achieved.
Patent Information
- Application Number
- CN202411891344.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
AI Technical Summary
The yarns produced by traditional vortex spinning process have limitations in terms of flexibility and wear resistance, and are difficult to meet the needs of high-end textiles.
A flexible vortex spinning fabric process including a substrate layer, an irradiated graft layer and a reinforcement layer is used to form a graft copolymer using a composite monomer composed of methyl acrylate and methacrylate, and a reinforcement layer is formed using silane-modified nanosilica on the irradiated graft layer.
Improves the flexibility and wear resistance of the fabric to meet the needs of high-end textiles.
Smart Images

Figure BDA0005200737000000071 
Figure BDA0005200737000000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of fabrics, and in particular to a compliant vortex spinning fabric and a spinning process. Background Art
[0002] Vortex spinning is a method of using air vortexes to condense and twist fibers that have been loosened into a single state into yarn. Since vortexes are used instead of mechanical twisting and condensation, no rotating parts are required, so the structure is simple and the spinning speed is high, generally 6 to 7 times higher than ring spinning. It is an efficient and energy-saving spinning method and is widely used in the textile industry. However, the yarn produced by traditional vortex spinning technology has limitations in terms of softness and wear resistance, and it is difficult to meet the needs of high-end textiles. Summary of the invention
[0003] In order to improve the softness and wear resistance of textiles, the present application provides a soft vortex spinning fabric and a spinning process.
[0004] In the first aspect, the present application provides a compliant vortex spinning fabric, which adopts the following technical solution: A compliant vortex spinning fabric comprises a substrate layer, an irradiation grafting layer and a reinforcement layer which are arranged in sequence; the raw materials of the irradiation grafting layer comprise solvent, methyl acrylate and methacrylate; the raw materials of the reinforcement layer comprise solvent and silane-modified nano-silicon dioxide.
[0005] By adopting the above technical scheme, a composite monomer composed of methyl acrylate and methacrylate is used to form a graft copolymer on the substrate layer, which can improve the wear resistance of the fabric while also improving the softness of the fabric; a reinforcement layer is formed on the irradiated graft layer using silane-modified nano-silica, which can further improve the softness and wear resistance of the fabric.
[0006] In a specific embodiment, the preparation method of the silane-modified nano-silicon dioxide comprises the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed uniformly to obtain a modified solution; The nano-silicon dioxide is stirred, and during the stirring process, the modification liquid is sprayed into the nano-silicon dioxide. After the spraying is completed, the stirring is continued, and the nano-silicon dioxide is dried to obtain the silane-modified nano-silicon dioxide.
[0007] By adopting the above technical scheme, γ-aminopropyltriethoxysilane is first dissolved in ethanol to obtain a modified liquid, and then the modified liquid is sprayed while stirring the nano-silica. After the spraying is completed, the stirring is continued and the nano-silica is dried to obtain silane-modified nano-silica.
[0008] In a specific embodiment, the weight ratio of the modified liquid to the nano-silicon dioxide is 1:(13-14).
[0009] By adopting the above technical solution, the ratio of the modified liquid to the nano-silicon dioxide is further limited, thereby improving the modification effect on the nano-silicon dioxide.
[0010] In the second aspect, the present application provides a spinning process for a compliant vortex spinning fabric, which adopts the following technical solution: A spinning process for a compliant vortex spinning fabric comprises the following steps: Graft modification: adding methyl acrylate and methacrylate to a solvent, stirring and mixing to obtain a graft treatment solution; selecting polyurethane fiber, cotton fiber, and polyester fiber as a substrate layer, placing them in an irradiation field, and then irradiating them, taking them out, immersing them in a graft treatment solution for grafting, taking them out, and drying them to form an irradiated graft layer on the substrate layer to obtain modified fibers; spinning: vortex spinning the modified fibers to obtain a base fabric; Post-treatment: adding silane-modified nano-silica to the solvent, stirring and mixing evenly to obtain a post-treatment liquid; immersing the base fabric in the post-treatment liquid for post-treatment, taking it out, and drying it to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric.
[0011] By adopting the above technical scheme, methyl acrylate and methacrylate are first added to a solvent to obtain a grafting treatment liquid, then the fibers of the substrate layer are subjected to grafting modification treatment, and then vortex spinning is performed to obtain a base cloth, and finally the base cloth is immersed in a post-treatment liquid containing silane-modified nano-silica for post-treatment to obtain a soft vortex spun fabric with good softness and wear resistance.
[0012] In a specific embodiment, in the grafting modification step, the weight ratio of the solvent, methyl acrylate and methacrylate in the grafting treatment solution is 100:(3-5):(3-5).
[0013] By adopting the above technical solution, the ratio of methyl acrylate, methacrylate and solvent is further limited, thereby improving the grafting modification effect on the substrate layer.
[0014] In a specific embodiment, in the grafting modification step, when the irradiation treatment is performed, the irradiation dose is 5-20 kGy.
[0015] By adopting the above technical solution, the irradiation dose of the irradiation grafting process is preferably 5-20 kGy, which can effectively improve the grafting efficiency, ensure the uniform distribution of the irradiation grafted layer, and enhance the physical properties and chemical stability of the fabric.
[0016] In a specific embodiment, in the grafting modification step, the temperature when the substrate layer is immersed in the grafting treatment liquid for grafting is 20-30°C.
[0017] In a specific embodiment, in the post-treatment step, the mass concentration of silane-modified nano-silica in the treatment solution is 10-15%.
[0018] In a specific embodiment, in the post-treatment step, the base fabric is immersed in a post-treatment liquid for post-treatment, taken out, and dried at 80-90° C. for 10-15 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a compliant vortex spinning fabric.
[0019] By adopting the above technical solution, the concentration of silane-modified nano-silicon dioxide in the treatment solution and the drying temperature and time during post-treatment are further limited, so that the reinforcement layer can be better formed.
[0020] In summary, the present application includes at least one of the following beneficial technical effects: 1. In this application, a composite monomer composed of methyl acrylate and methacrylate is used to form a graft copolymer on the substrate layer, which can improve the wear resistance of the fabric and the flexibility of the fabric; a reinforcement layer is formed on the irradiated graft layer using silane-modified nano-silica, which can further improve the flexibility and wear resistance of the fabric; 2. In the present application, γ-aminopropyltriethoxysilane is first dissolved in ethanol to obtain a modified liquid, and then the modified liquid is sprayed while stirring the nano-silica. After spraying, stirring is continued and drying is performed to obtain silane-modified nano-silica; 3. In the method of the present application, methyl acrylate and methacrylate are first added to a solvent to obtain a grafting treatment liquid, and then the fibers of the substrate layer are grafted and modified, and then vortex spinning is performed to obtain a base cloth, and finally the base cloth is immersed in a post-treatment liquid containing silane-modified nano-silica for post-treatment to obtain a flexible vortex spinning fabric with good flexibility and wear resistance. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] All raw materials in the examples are commercially available.
[0023] Preparation Example Preparation Example 1 Preparation Example 1 provides a method for preparing silane-modified nano-silicon dioxide, comprising the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed evenly to obtain a modified liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, water and ethanol is 5:2:18; The nano-silica was stirred, and during the stirring process, the modified liquid was sprayed into the nano-silica. After the spraying was completed, the stirring was continued for 0.5 h, and the nano-silica was dried at 100° C. for 0.5 h to obtain silane-modified nano-silica; wherein the weight ratio of the modified liquid to the nano-silica was 1:12.5.
[0024] Preparation Example 2 Preparation Example 2 provides a method for preparing silane-modified nano-silicon dioxide, comprising the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed evenly to obtain a modified liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, water and ethanol is 5:2:18; The nano-silica was stirred, and during the stirring process, the modified liquid was sprayed into the nano-silica. After the spraying was completed, the stirring was continued for 0.5 h, and the nano-silica was dried at 100° C. for 0.5 h to obtain silane-modified nano-silica; wherein the weight ratio of the modified liquid to the nano-silica was 1:13.
[0025] Preparation Example 3 Preparation Example 3 provides a method for preparing silane-modified nano-silicon dioxide, comprising the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed evenly to obtain a modified liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, water and ethanol is 5:2:18; The nano-silica was stirred, and during the stirring process, the modified liquid was sprayed into the nano-silica. After the spraying was completed, the stirring was continued for 0.5 h, and the nano-silica was dried at 100° C. for 0.5 h to obtain silane-modified nano-silica; wherein the weight ratio of the modified liquid to the nano-silica was 1:13.5.
[0026] Preparation Example 4 Preparation Example 4 provides a method for preparing silane-modified nano-silicon dioxide, comprising the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed evenly to obtain a modified liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, water and ethanol is 5:2:18; The nano-silica was stirred, and during the stirring process, the modified liquid was sprayed into the nano-silica. After the spraying was completed, the stirring was continued for 0.5 h, and the nano-silica was dried at 100° C. for 0.5 h to obtain silane-modified nano-silica; wherein the weight ratio of the modified liquid to the nano-silica was 1:14.
[0027] Preparation Example 5 Preparation Example 5 provides a method for preparing silane-modified nano-silicon dioxide, comprising the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed evenly to obtain a modified liquid; wherein the weight ratio of γ-aminopropyltriethoxysilane, water and ethanol is 5:2:18; The nano-silica was stirred, and during the stirring process, the modified liquid was sprayed into the nano-silica. After the spraying was completed, the stirring was continued for 0.5 h, and the nano-silica was dried at 100° C. for 0.5 h to obtain silane-modified nano-silica; wherein the weight ratio of the modified liquid to the nano-silica was 1:14.5. Example
[0028] Example 1 Embodiment 1 provides a spinning process for a compliant vortex spinning fabric, comprising the following steps: Graft modification: add methyl acrylate and methacrylate to the solvent, stir and mix evenly to obtain a graft treatment solution; select polyurethane fiber, cotton fiber, and polyester fiber as the substrate layer, place them in an irradiation field, and perform irradiation treatment with an irradiation dose of 15 kGy, then take them out, immerse them in the graft treatment solution for grafting at 25°C, take them out, dry them, and form an irradiated graft layer on the substrate layer to obtain modified fibers; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:2:2; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; Spinning: vortex spinning the modified fiber to obtain the base fabric; Post-treatment: Add the silane-modified nano-silica in Preparation Example 1 to the solvent, stir and mix evenly to obtain a post-treatment liquid; immerse the base fabric in the post-treatment liquid for post-treatment, with a bath ratio of 1:10; take it out and dry it at 80°C for 15 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric; wherein the solvent is ethanol, and the mass concentration of the silane-modified nano-silica in the treatment liquid is 10%.
[0029] Example 2 The difference between Example 2 and Example 1 is that, in the post-treatment, the silane-modified nano-silica in Preparation Example 2 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the remaining steps are consistent with Example 1.
[0030] Example 3 The difference between Example 3 and Example 1 is that, in the post-treatment, the silane-modified nano-silica in Preparation Example 3 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the remaining steps are consistent with Example 1.
[0031] Example 4 The difference between Example 4 and Example 1 is that, in the post-treatment, the silane-modified nano-silica in Preparation Example 4 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the remaining steps are consistent with Example 1.
[0032] Example 5 The difference between Example 5 and Example 1 is that, in the post-treatment, the silane-modified nano-silica in Preparation Example 5 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the remaining steps are consistent with Example 1.
[0033] Example 6 The difference between Example 6 and Example 3 is that, in the grafting modification, methyl acrylate and methacrylate are added to a solvent, stirred and mixed evenly to obtain a grafting treatment liquid; polyurethane fiber, cotton fiber, and polyester fiber are selected as the substrate layer, placed in an irradiation field, and irradiated with an irradiation dose of 15 kGy, then taken out, immersed in the grafting treatment liquid for grafting at 25°C, taken out, and dried to form an irradiated grafted layer on the substrate layer to obtain modified fiber; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:3:3; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; and the remaining steps are consistent with Example 3.
[0034] Example 7 The difference between Example 7 and Example 3 is that, in the grafting modification, methyl acrylate and methacrylate are added to the solvent, stirred and mixed evenly to obtain a grafting treatment liquid; polyurethane fiber, cotton fiber, and polyester fiber are selected as the substrate layer, placed in an irradiation field, and irradiated with an irradiation dose of 15 kGy, then taken out, immersed in the grafting treatment liquid for grafting at 25°C, taken out, and dried to form an irradiated grafted layer on the substrate layer to obtain modified fiber; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:4:4; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; and the remaining steps are consistent with Example 3.
[0035] Example 8 The difference between Example 8 and Example 3 is that, in the grafting modification, methyl acrylate and methacrylate are added to a solvent, stirred and mixed evenly to obtain a grafting treatment liquid; polyurethane fiber, cotton fiber, and polyester fiber are selected as the substrate layer, placed in an irradiation field, and irradiated with an irradiation dose of 15 kGy, then taken out, immersed in the grafting treatment liquid for grafting at 25°C, taken out, and dried to form an irradiated grafted layer on the substrate layer to obtain modified fibers; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:5:5; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; and the remaining steps are consistent with Example 3.
[0036] Example 9 The difference between Example 9 and Example 3 is that, in the grafting modification, methyl acrylate and methacrylate are added to the solvent, stirred and mixed evenly to obtain a grafting treatment liquid; polyurethane fiber, cotton fiber, and polyester fiber are selected as the substrate layer, placed in an irradiation field, and irradiated with an irradiation dose of 15 kGy, then taken out, immersed in the grafting treatment liquid for grafting at 25°C, taken out, and dried to form an irradiated grafted layer on the substrate layer to obtain modified fiber; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:6:6; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; and the remaining steps are consistent with Example 3.
[0037] Example 10 The difference between Example 10 and Example 7 is that the post-treatment is as follows: the silane-modified nano-silica in Preparation Example 3 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the base fabric is immersed in the post-treatment liquid for post-treatment, and the bath ratio is 1:10; it is taken out and dried at 85°C for 13 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric; wherein the solvent is ethanol, and the mass concentration of silane-modified nano-silica in the treatment liquid is 12.5%; and the remaining steps are consistent with Example 7.
[0038] Embodiment 11 The difference between Example 11 and Example 7 is that the post-treatment is as follows: the silane-modified nano-silica in Preparation Example 3 is added to the solvent, stirred and mixed evenly to obtain a post-treatment liquid; the base fabric is immersed in the post-treatment liquid for post-treatment, and the bath ratio is 1:10; it is taken out and dried at 90°C for 10 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric; wherein the solvent is ethanol, and the mass concentration of the silane-modified nano-silica in the treatment liquid is 15%; and the remaining steps are consistent with Example 7.
[0039] Comparative Example Comparative Example 1 Comparative Example 1 provides a spinning process for a fabric, comprising the following steps: Spinning: vortex spinning polyurethane fiber, cotton fiber and polyester fiber to obtain base fabric; wherein the weight ratio of polyurethane fiber, cotton fiber and polyester fiber is 3:10:3; Post-treatment: Add the silane-modified nano-silica in Preparation Example 1 to the solvent, stir and mix evenly to obtain a post-treatment liquid; immerse the base fabric in the post-treatment liquid for post-treatment, with a bath ratio of 1:10; take it out and dry it at 80°C for 15 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric; wherein the solvent is ethanol, and the mass concentration of the silane-modified nano-silica in the treatment liquid is 10%.
[0040] Comparative Example 2 Comparative Example 2 provides a spinning process for a fabric, comprising the following steps: Graft modification: add methyl acrylate and methacrylate to the solvent, stir and mix evenly to obtain a graft treatment solution; select polyurethane fiber, cotton fiber, and polyester fiber as the substrate layer, place them in an irradiation field, and perform irradiation treatment with an irradiation dose of 15 kGy, then take them out, immerse them in the graft treatment solution for grafting at 25°C, take them out, dry them, and form an irradiated graft layer on the substrate layer to obtain modified fibers; wherein the solvent is ethanol, and the weight ratio of the solvent, methyl acrylate, and methacrylate is 100:2:2; the weight ratio of the polyurethane fiber, cotton fiber, and polyester fiber is 3:10:3; Spinning: The modified fiber is subjected to vortex spinning to obtain fabric.
[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that, in the grafting modification, methyl acrylate is added to the solvent, stirred and mixed evenly to obtain a grafting treatment liquid; the weight ratio of the solvent to methyl acrylate is 100:4; and the remaining steps are consistent with Example 1.
[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that, in the grafting modification, methacrylate is added to the solvent, stirred and mixed evenly to obtain a grafting treatment liquid; the weight ratio of the solvent to the methacrylate is 100:4; and the remaining steps are consistent with Example 1.
[0043] Performance test: Softness: 150 testers were selected and divided into 15 groups, corresponding to Examples 1-11 and Comparative Examples 1-4, with 10 testers in each group. The fabrics were felt, the softness was evaluated, and the scores were given on a scale of 1-10. The average of each group was taken. The higher the score, the better the softness of the fabric.
[0044] Wear resistance: Use domestic No. 400 sandpaper as abrasive to rub the fabric. The friction length is 55mm±2mm and the friction speed is 60 times / min. After 300 reciprocating frictions, calculate the friction weight loss rate. Friction weight loss rate = (mass before friction - mass after friction) / mass before friction * 100%. The smaller the friction weight loss rate, the better the wear resistance.
[0045] Table 1 Fabric performance test results Combining Example 1 and Comparative Examples 1-4, the softness and wear resistance of the fabric in Example 1 are better. It can be seen that when preparing the fabric, a composite monomer composed of methyl acrylate and methacrylate is first used to form a graft copolymer on the substrate layer, and then a reinforcement layer is formed on the irradiated graft layer using silane-modified nano-silica, which can improve the softness and wear resistance of the fabric.
[0046] Combined with Examples 1-5, the wear resistance of the fabrics in Examples 2-4 is better. It can be seen that when preparing silane-modified nano-silica, the ratio of the modified liquid to the nano-silica is preferably 1:(13-14), and the performance of the silane-modified nano-silica is better.
[0047] In combination with Example 3 and Examples 6-9, the softness and wear resistance of the fabric in Example 6-8 are both good. It can be seen that when preparing the grafting treatment liquid, the ratio of solvent, methyl acrylate, and methacrylate in the grafting treatment liquid is preferably 100:(3-5):(3-5), which has a better grafting modification effect on the substrate layer.
[0048] Combining Example 7, Example 10 and Example 11, the softness and wear resistance of the fabric in Example 10 are better. It can be seen that when the base fabric is post-treated, the processing conditions in Example 10 are the best, so that the fabric with the best performance is finally obtained.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but such modifications are protected by patent law as long as they are within the scope of the claims of the present application.
Claims
1. A soft vortex spinning fabric, characterized by: The invention comprises a substrate layer, a radiation grafting layer and a reinforcement layer which are arranged in sequence; the raw materials of the radiation grafting layer comprise solvent, methyl acrylate and methacrylate; the raw materials of the reinforcement layer comprise solvent and silane-modified nano-silicon dioxide.
2. The compliant vortex spinning fabric according to claim 1, characterized in that: The preparation method of the silane-modified nano-silicon dioxide comprises the following steps: γ-aminopropyltriethoxysilane, water and ethanol are stirred and mixed uniformly to obtain a modified solution; The nano-silicon dioxide is stirred, and during the stirring process, the modification liquid is sprayed into the nano-silicon dioxide. After the spraying is completed, the stirring is continued, and the nano-silicon dioxide is dried to obtain the silane-modified nano-silicon dioxide.
3. The compliant vortex spinning fabric according to claim 2, characterized in that: The weight ratio of the modified liquid to the nano-silicon dioxide is 1:(13-14).
4. A spinning process for a compliant vortex spinning fabric as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: Graft modification: adding methyl acrylate and methacrylate to a solvent, stirring and mixing evenly to obtain a graft treatment solution; selecting polyurethane fiber, cotton fiber, and polyester fiber as a substrate layer, placing them in an irradiation field, and then taking them out, immersing them in a graft treatment solution for grafting, taking them out, and drying them to form an irradiated graft layer on the substrate layer to obtain a modified fiber; Spinning: vortex spinning the modified fiber to obtain the base fabric; Post-treatment: adding silane-modified nano-silica to the solvent, stirring and mixing evenly to obtain a post-treatment liquid; immersing the base fabric in the post-treatment liquid for post-treatment, taking it out, and drying it to form a reinforcement layer on the irradiated grafted layer to obtain a soft vortex spinning fabric.
5. The spinning process of a compliant vortex spinning fabric according to claim 4, characterized in that: In the grafting modification step, the weight ratio of the solvent, methyl acrylate and methacrylate in the grafting treatment solution is 100:(3-5):(3-5).
6. The spinning process of a compliant vortex spinning fabric according to claim 4, characterized in that: In the grafting modification step, when irradiation treatment is performed, the irradiation dose is 5-20 kGy.
7. The spinning process of a compliant vortex spinning fabric according to claim 4, characterized in that: In the grafting modification step, the temperature of the substrate layer when immersed in the grafting treatment liquid for grafting is 20-30°C.
8. The spinning process of a compliant vortex spinning fabric according to claim 4, characterized in that: In the post-treatment step, the mass concentration of silane-modified nano-silica in the treatment solution is 10-15%.
9. The spinning process of a compliant vortex spinning fabric according to claim 8, characterized in that: In the post-treatment step, the base fabric is immersed in a post-treatment liquid for post-treatment, taken out, and dried at 80-90° C. for 10-15 minutes to form a reinforcement layer on the irradiated grafted layer to obtain a compliant vortex spinning fabric.